Physiotherapeutic diagnostics in the Intensive Care Unit (ICU): an integrative review (Research, Society and Development, 2022)
Studies bring up the relationship between assessment and physiotherapeutic intervention in the ICU in a vision of function, independence and functionality, and also bring up the importance of performing functional assessments in this environment. Therefore, this study aimed to discuss and analyze the physiotherapeutic diagnoses in the intensive care unit, through an integrative review of literature with searches in the portals BVS and PubMed, with descriptors: physiotherapy specialty, diagnosis, intensive care unit and health evaluation. After selection, 9 articles were included, generating discussions about: concepts, definition, importance and contributions of the physiotherapeutic diagnosis in the intensive care unit, the main physiotherapeutic diagnoses in the ICU and the instruments used, potentialities, weaknesses/barriers, gaps and perspectives. Based on this review, we can infer that the assessment of the physiotherapist working in intensive care is essential and a sine qua nom condition in the ICU, because anticipation of more effective care and early rehabilitation will lead to more favorable outcomes for the patient. There are several physiotherapeutic diagnoses, instruments for creation and their contexts of application in the ICU, to enhance information on health conditions and the functional status of individuals, as well as the ability to interact in the ICU.